2021
DOI: 10.1093/jac/dkab241
|View full text |Cite
|
Sign up to set email alerts
|

Added value of rapid respiratory syndromic testing at point of care versus central laboratory testing: a controlled clinical trial

Abstract: Background Virus-associated respiratory infections are in the spotlight with the emergence of SARS-CoV-2 and the expanding use of multiplex PCR (mPCR). The impact of molecular testing as a point-of-care test (POCT) in the emergency department (ED) is still unclear. Objectives To compare the impact of a syndromic test performed in the ED as a POCT and in the central laboratory on length of stay (LOS), antibiotic use and single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…Finally, we found no signi cant difference between antibiotic prescriptions between the ROST and standard arm at either site. This is consistent with other published randomized trials in adult (8, 9,12,15) and paediatric (12) populations, in addition to non-randomized trials in paediatric (18, 21) and adult (26) populations. This highlights that rapid test results in and of themselves are unlikely to change antimicrobial prescribing practice (13).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Finally, we found no signi cant difference between antibiotic prescriptions between the ROST and standard arm at either site. This is consistent with other published randomized trials in adult (8, 9,12,15) and paediatric (12) populations, in addition to non-randomized trials in paediatric (18, 21) and adult (26) populations. This highlights that rapid test results in and of themselves are unlikely to change antimicrobial prescribing practice (13).…”
Section: Discussionsupporting
confidence: 92%
“…Regarding our secondary outcomes, we found a signi cantly shorter TAT in the ROST arm with results reported in a mean 26 hours or more before the standard arm. Signi cantly reduced TAT with rapid testing is a consistent nding in rapid/ROST studies of various designs and quality (5,8,15,20,23,25).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…A large number of studies have evaluated the diagnostic performance of FA-PP compared to standard culture in patients with suspected LRTBI [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] ; nonetheless, cross-study comparison is not straightforward due to differences in potentially impactful parameters, such as patient's baseline clinical condition, hospitalization ward (ICU vs. non-ICU), LRTBI features (i.e., associated or not with MV), timing of FA-PP testing after hospital admission, specimens used (endotracheal aspirates vs. bronchoscopic specimens), and most importantly, whether or not EAT was in place at the time of testing. Despite these dissimilarities, all studies consistently showed the superior sensitivity of FA-PP for detection of all on-panel bacterial targets [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] . In line with this, we found that, compared with culture, FA-PP increased the number of specimens reported as positive by approximately 70% and the total number of bacterial targets detected by around 120%, irrespective of their nature.…”
Section: Discussionmentioning
confidence: 99%
“…Standard semiquantitative culture-based and antimicrobial susceptibility testing procedures performed on endotracheal aspirates or bronchoscopic specimens are lengthy, returning results approximately 48–72 h after specimen reception. The use of molecular diagnostic approaches that allow rapid bacterial identification and documentation of the presence of genotypic resistance traits in the causative bacteria may provide clinically actionable results within 2 h. One such approach is the BioFire® FilmArray® Pneumonia/Pneumonia plus Panel (FA-PP) (BioFire Diagnostics, LLC, Salt Lake City, UT), a multiplex PCR panel that allows detection of 15 bacteria commonly involved in VA-LRTBI, providing semiquantitative estimates of bacterial load and seven genetic markers of antibiotic resistance (mecA/C and MREJ, blaCTX-M,blaKPC, blaVIM, blaOXA-48-like, blaIMP, blaNDM) This test has been extensively evaluated and proven to increase the diagnostic yield in LRTBI compared with standard culture-based methods [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] . FA-PP shows great promise in improving the therapeutic management of VA-LRTBI, however, its positioning in laboratory diagnostic algorithms remains to be defined [22] .…”
Section: Introductionmentioning
confidence: 99%